KEMAMPUAN PENYELESAIAN SOAL CERITA DALAM PEMBELAJARAN MATEMATIKA DENGAN MODEL PROBLEM BASED LEARNING DI SEKOLAH DASAR - Jasman, Putri Anas; Zainil, Melva; Fitria, Yanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
THE ABILITY TO SOLVE THE STORY QUESTIONS IN LEARNING MATHEMATICS WITH PROBLEM BASED LEARNING MODEL IN ELEMENTARY SCHOOL Abstract This study aimed to investigate the ability to solve the story questions in learning mathematics with problem based learning model in elementary school. This research was a quasi experimental research with the research design used is Non Equivalent Control Group Design. The sample was determined by cluster random sampling technique. The sample in this research was a class V SDN 03 2x11 Enam Lingkung and SDN 12 2x11 Enam Lingkung. The results of this study obtained the average value of experimental class using Problem Based Learning model is 76 higher than the control class using conventional learning 67.2. Based on the results of hypothesis test calculation obtained tcount of 2.17 and ttable with a significant level of 0.05 and dk 48 is 2.01 indicates that thitung> ttabel, so H0 rejected and Ha can be accepted. Therefore, it can be concluded that the ability to solve the story questions in learning with problem based learning model in elementary school gave significant results. Key words: model problem based learning, ability to solve the story questions